METHODOLOGICAL BASIS OF USING MODERN PEDAGOGICAL TECHNOLOGIES IN FORMING TECHNICAL-TACTICAL SKILLS IN WRESTLERS (Eureka Journal of Physical and Chemical Research, 2026)
This scientific article analyzes the methodological foundations of the use of modern pedagogical technologies in the formation of technical and tactical skills in wrestlers. The study highlights the theoretical and practical aspects of the development of technical movements and tactical thinking in wrestling, and considers innovative approaches to the effective organization of the training process. It also substantiates the possibilities of developing technical and tactical training in athletes through the use of interactive methods, game technologies, simulated game situations and digital tools.
Keywords: Wrestling, technical and tactical skills, pedagogical technologies, sports training, interactive methods, game technologies, tactical thinking, simulated situations, sports skills, methodological foundations.